2015
DOI: 10.1080/00071668.2015.1077203
|View full text |Cite
|
Sign up to set email alerts
|

Footpad dermatitis and pain assessment in turkey poults using analgesia and objective gait analysis

Abstract: The relationships between litter moisture, footpad dermatitis (FPD) and pain in medium-heavy turkey strains was studied by gait analysis in two medium-heavy with and without analgesia (betamethasone or bupivacaine).The relationship between FPD and litter moisture was linear above a breakpoint of 49% litter moisture, and there were no differences between the two breeds in susceptibility to FPD.Gait analysis showed higher impulse, single support time, stride time and stance time in breed A compared to breed B. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 31 publications
1
32
0
1
Order By: Relevance
“…The increase in footpad lesions (week 16) may also relate to the decrease in mobility, as footpad lesions have been associated with pain ( 5 , 6 ). Similar results have been seen in turkeys previously, with a higher incidence of footpad lesions present at higher SD in 12-week old hens and 16-week old toms at slaughter ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in footpad lesions (week 16) may also relate to the decrease in mobility, as footpad lesions have been associated with pain ( 5 , 6 ). Similar results have been seen in turkeys previously, with a higher incidence of footpad lesions present at higher SD in 12-week old hens and 16-week old toms at slaughter ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Martrenchar et al also evaluated bird mobility, and found that as SD increased, gait scores became poorer, indicative of poorer mobility ( 2 ). The authors hypothesized that this may be due to reduced activity, although it may also relate to the increased incidence of footpad lesions as they have been associated with pain in previous studies ( 6 ). In addition to increased litter moisture, litter temperature has also been shown to increase at higher SD ( 7 ).…”
Section: Introductionmentioning
confidence: 97%
“…Lesions similar to those observed in broiler chickens were encountered in turkeys, housed on wet litter (Martland 1984). Recently, an examination of the pain caused by foot pad dermatitis, in the context of turkey poults, noted that the condition may have an adverse effect on mobility and linked it to weight loss (Da Costa et al 2014;Wyneken et al 2015). High humidity in poultry facilities was also highlighted as a predisposing factor (Bruce et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the results of the current experiment and the parallel study in Italy (Veldkamp et al 2017) confirm the importance of DEB and the role that soya bean meal has in increasing litter moisture and the prevalence of FPD. Combined with evidence that FPD may be painful (Sinclair et al 2015;Weber Wyneken et al 2015), it is imperative that regular monitoring and amelioration of litter conditions are incorporated into flock management procedures to minimise FPD; specifically, the increase in litter moisture with time must be minimised (Wu and Hocking 2011;Weber Wyneken et al 2015). A simple but effective system for litter scoring was recently published (Giacomelli et al 2018) that will facilitate this process even if manipulation of dietary composition and DEB will be limited by practical and economic constraints.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of foot pad dermatitis (FPD) in growing poultry is an adverse welfare and economic factor that is closely related to high concentrations of litter moisture (Wu and Hocking 2011;Weber Wyneken et al 2015). The banning of animal by-products as protein sources in diets for livestock in Europe (European Commission Decisions No.…”
Section: Introductionmentioning
confidence: 99%